Occurrence of Alternaria japonica on Seeds of Wild and Cultivated Rocket. Issue 5 (17th July 2014) - Gilardi, Giovanna; Demarchi, Stefano; Ortu, Giuseppe; Gullino, Maria Lodovica; Garibaldi, Angelo
Abstract In vitro evaluation was carried out on seed samples of wild and cultivated rocket cultivars, most frequently grown in Italy, and obtained from farms affected by the leaf spot caused by Alternaria japonica in Piedmont and Lombardy during the fall of 2010. Twelve seed samples were collected and assayed for the presence of A. japonica. The pathogen was isolated only from not disinfected seeds. Among the two seed samples of cultivated rocket (Eruca vesicaria), only one was infected by A. japonica at a level of one infected seed out of 800. Four out of ten samples of wild (Diplotaxis tenuifolia) rocket seeds were contaminated by A. japonica with the highest level of infection detected in a single sample of 3 out of 800. All tested isolates of A. japonica obtained from seeds were pathogenic on both wild and cultivated rocket.